Vibrational performance modeling for coupling of a full-ellipsoid shell with a cylindrical shell with a focus on flexibility at coupling and boundary conditions via the GDQ-meshless method. (November 2022) - Sobhani, Emad
Abstract: This paper analyzes the vibrational features of the Coupled Full Ellipsoid-Cylindrical Shell (CFECS) structures for the first time. In addition, for the first-time use, the artificial spring method is implemented to indicate the trace of elasticity conditions at Coupling Conditions (CCs) and Boundary Conditions (BCs) on the Natural frequencies (NFs) of the CFECS structures. Additionally, the primary relationships of the CFECS are determined by engaging the First Order Shear Deformation Theory (FOSDT) and Comprehensive Shell Theory (CST) for Full Ellipsoid (FE) and Cylindrical (C) shell segments of the CFECS separately. Moreover, the Motion Equations (MEs) of the CFECS's shell segments are discovered by implementing Hamilton's principle. Supplementary, a well-organized differential solution strategy, the Generalized Differential Quadrature (GDQ) technique, is applied to discretize the MEs related to the CFECS. Extra, the determination of the eigenvalues is realized to discover the NFs of the CFECS structures. Since there has been no investigation of this structure in the literature, the NFs determined by the submitted procedure are validated with the outputs measured by FEM-based commercial software. It should be revealed that the maximum difference was detected as less than 1.0%. Accordingly, the numerical results proposed here can be employed as the benchmark. Finally, various parameters that can affect the NFs of the CFECS, comprising geometrical, CCs, and BCs, are thoroughly investigated here.